HUMAN RIGHTS DEFENDERS: TANGGUNG JAWAB NEGARA DAN PERLINDUNGAN HUKUM PEMBELA HAM PEREMPUAN - Hayati, Dyah Kemala (Esensi Hukum, 2023)
The concept of women human rights defenders is not as an attempt to exclude women from the role of human rights defenders in general, but because their involvement in human rights defense efforts is often underrecognized and invisible. Inequality in the relationship between men and women is still a marginal discussion due to the inferiority of women. The idea that women's human rights are part of human rights (women's rights are human rights), including defenders of their human rights, needs to be fought for. Local social, religious and cultural values ​​are problematic for women's human rights defenders. State responsibility and legal protection for women human rights defenders is a common concern. Reflecting on the Declaration of Human Rights Defenders shows that the world community has guaranteed the rights of every human being. The approach used is a normative juridical approach with Statute Approach. This research approach is approach. Issues of human rights, state responsibility, and legal protection for women human rights defenders are not taken seriously by the state. The lack of provisions to protect women human rights defenders places them in a vulnerable and dangerous situation. There is a legal vacuum to protect women human rights defenders. This can be used as a reference in developing security protection for women human rights defenders and their institutions because they are vulnerable to violence and criminalization by various groups. Keywords: Responsibility, Protection, Human Rights Defenders, Women